O ENSINO DE MATEMÁTICA NA EDUCAÇÃO BÁSICA, POTENCIALIZADO ATRAVÉS DE MATERIAL DIDÁTICO VIRTUAL - Brizzi, Maristela L. S.; Pereira, Tânia M.; Soares, Carine G. T.; Piva, Claudia; Dalabrida, Lecir D. (Salão do Conhecimento, 2013)
Resumo